Implementation of the Family Hope Program (PKH) in Bandung Regency, West Java Province - Oki Candra Supriyadi; Wirman Syafri; Layla Kurniawati (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
This study aims to describe and explain the Family Hope Program (PKH) in Bandung Regency. The research approach used is descriptive qualitative, with data collection methods used are interviews, observations and documents related to the problem being studied. Simply put, PKH is a conditional social assistance provided to Beneficiary Families (KPM) with certain conditions that have been registered in the Ministry of Social Affairs' DTKS. Integrated Social Welfare Data (DTKS) is a data that serves as a reference source for the implementation of social welfare, in this case the data contains data on social assistance needs and social welfare services. This DTKS is to be used as a reference basis in the distribution of social assistance, Indonesia has implemented the Family Hope Program since 2007. This study uses the implementation theory approach from Van Metter and Van Horn (1975) which includes 6 variables, namely standards/measures and policy objectives, policy sources, characteristics or characteristics of implementing agencies, attitudes of implementers, communication between related organizations and implementation activities, economic, social, and political environments. This study shows that the implementation of the Family Hope Program (PKH) in Bandung Regency has an impact on improving the welfare of poor families. However, in its implementation, PKH assistants are still found to have double jobs or work elsewhere.